A Low Noise Amplifier Chain for Digital Satellite Radio Applications - Röber, Jürgen; Bänisch, Andreas; Fischer, Georg; Weigel, Robert (IEEE International Symposium on Circuits and Systems (ISCAS), 2015)
This paper contains the development and verification of low noise amplifier stages (LNA) within the framework of a front-end for digital satellite radio diversity receiver operating around 2.3 GHz. First, a low noise high gain LNA is developed to reach the high requirements of satellite radio reception. Therefore a single-ended cascode architecture is chosen. The simulated noise figure is 0.58 dB and the gain is 19.87 dB. Second, a differential stage is designed to fulfill the specification with regards to backward isolation and common-mode rejection. This circuit has a measured gain of 10.15 dB and a backward isolation of -43.24 dB. Furthermore, the two stages are combined by an integrated balun and the overall performance is verified. Due to the good noise performance of the first stage, the overall noise figure is 0.64 dB, the gain is 29.83 dB and the backward isolation is - 76.07 dB. All in all the whole circuit has a current consumption of 25.40 mA. Finally the LNA performance is compared with other state-of-the-art LNAs.
elib2cris::1512001600,roeber2015
Keywords: LNA; low noise; high gain; differential; distortion canceller; CCPDC